Effects of inorganic and compost tea fertilizers application on the taxonomic and functional microbial diversity of the purslane rhizosphere - Carrascosa, Angel; Pascual, Jose Antonio; López-García, Álvaro; Romo-Vaquero, María; De Santiago, Ana; Ros, Margarita; Petropoulos, Spyridon A.; Alguacil, Maria Del Mar (Frontiers in Plant Science, 2023)
Soil fertility is a major determinant of plant-microbial interactions, thus, directly and indirectly affecting crop productivity and ecosystem functions. In this study, we analysed for the first time the effects of fertilizer addition on the cropping of purslane (Portulaca oleracea) with particular attention to the taxonomic and functional characteristics of their associated soil microbiota. We tested the effects of different doses of inorganic fertilization differing in the amount of N:P:K namely IT1 (300:100:100); IT2 (300:200:100); IT3 (300:200:200); and IT4 (600:100:100) (ppm N:P:K ratio) and organic fertilization (compost tea) which reached at the end of the assay the dose of 300 ppm N. Purslane growth and soil quality parameters and their microbial community structure, abundance of fungal functional groups and prevailing bacterial metabolic functions were monitored. The application of compost tea and inorganic fertilizers significantly increased the purslane shoot biomass, and some soil chemical properties such as pH and soil enzymatic activities related to C, N and P biogeochemical cycles. The bacterial and fungal community compositions were significantly affected by the organic and chemical fertilizers input. The majority of inorganic fertilization treatments decreased the fungal and bacterial diversity as well as some predictive bacterial functional pathways. These findings suggest that the inorganic fertilization might lead to a loss of microbial functioning. However, further research is still needed to investigate the effects of fertilizations on purslane productivity under commercial field conditions.